Modification of Land Cultivation Techniques in Cultivating Tomato Plants (Solanum lycopersicum) - A. Miftahurohmat; Maulana Ibrahim; Andriani Eka Prihatiningrum (Universitas Muhammadiyah Sidoarjo, 2023)
Tomato (Solanum lycopersicum) is one of the horticultural crops that has high economic value and is widely cultivated throughout the world. Tomato cultivation requires special attention, especially on tillage techniques to achieve maximum results. The purpose of this study was to determine soil processing techniques in the cultivation of tomato plants (Solanum Lycopersicum) in Claket village, Mojokerto Regency. The method used is observation with discrimination. The results of the study were that the land processing technique is with No Tillage (TOT) / Zero Tillage, Minimum Tillage and Maximum Tillage. The tillage technique applied by the Farmer Group in Claket village, Mojokerto regency is a maximum tillage technique, where the tillage process is carried out from the initial stage to the end and the land is ready for planting, so that the tomato plants produced are very good and of high quality.